A novel mutation in GCK gene: Beware of SGA child with diabetic mother. (November 2021) - Tagliaferri, F.; Grosso, C.; Balbo, M.; Bracciolini, G.; Bertelli, E.; Secco, A.; Salina, A.; Aloi, C.; Gallo, M.; Felici, E.
Abstract: MODY is a monogenic, autosomal dominant form of diabetes mellitus. MODY can be caused by mutations in several genes; glucokinase (GCK) accounts for 30–50% of the cases. The diagnosis can be suspected in early-onset diabetes with atypical features for type 1/type 2. Treatment is usually not recommended. A 5-year-old girl came to our attention for occasional episodes of hyperglycaemia. She was born at term, her birth weight was small for gestational age. At the beginning of her pregnancy, her mother was already on insulin therapy for impaired fasting glucose levels, detected before conception and confirmed in the first weeks of gestation. She was treated with insulin until the childbirth without further investigations. The patient was asymptomatic and in good clinical condition. Basal blood tests have shown a fasting plasma glucose of 125 mg/dl, an HbA1c of 6.5%. Antibodies against islet cells, anti-GAD and anti-ZNT8 antibodies were all negative. A 2-h oral glucose tolerance test was performed and underlined an impaired glucose tolerance. HLA haplotypes were screened, excluding susceptibility. GCK Sanger Sequencing identified a novel heterozygous variant. It is not described as a classical mutations. The analysis has been extended to the parents, finding out the same variant in her mother. To our knowledge this mutation has not been described previously; we believe that this variant is responsible for MODY2 due to FBG and Hb1Ac of all the affected members of family. We suggest high suspicion of an underlying GCK variant in SGA children with hyperglycaemia born to a diabetic mother.